Program Pendidikan Akhlak Qur'ani untuk Guru di Pesantren Hidayatullah - Ansari, Ilham (Tawazun: Jurnal Pendidikan Islam, 2021)
Education is a core component in building civilization. The development and progress of a civilization will not be realized unless there is an educated society. Educated society is people who care about the world of education, without education it is impossible to realize the lofty ideals of humans. Education in schools is the basis for the formation of individuals in an effort to fulfill the provision of nutritional knowledge so that their roles are able to adapt as well as color social diversity in society. Therefore, the quality of education is a prerequisite for shaping individual morals and mentality in priority for teachers with their best programs to become a link in an effort to create a superior generation under the auspices of Islam. Abstrak Tujuan penelitian ini guna memperoleh informasi lebih lanjut mengenai program pendidikan akhlak di Pesantren Hidayatullah Depok. Pendidikan merupakan komponen inti dalam membangun peradaban. Perkembangan kemajuan sebuah peradaban tidak akan terwujud kecuali terdapat di dalamnya masyarakat yang terdidik. Masyarakat terdidik ialah orang-orang yang peduli terhadap dunia pendidikan, tanpa pendidikan maka mustahil akan mampu mewujudkan cita-cita luhur manusia. Pendidikan di sekolah merupakan dasar pembentukan individu dalam upaya pemenuhan bekal nutrisi ilmu agar peranannya mampu beradaptasi sekaligus mewarnai keberagaman sosial di masyarakat. Maka dari itu mutu pendidikan menjadi syarat dalam pembentukan akhlak serta mentalitas individu secara prioritas yang diperani oleh para guru dengan program terbaiknya guna menjadi mata rantai sebagai upaya mewujudkan generasi unggul dalam naungan Islam.